Pengaruh Senam Otak Terhadap Kemampuan Kognitif Siswa di MTS Al-Hikmah Proto - Fristi Sila Aulia Ivanka; Ihdina Hikmatun Ni’mah; Novi Tri Fadila; Muhammad Dava Ardian Syah; Santi Listiarini; Kholisah Qudrotun Nada; Yusril Ihza Maulana; Nurul Aktifah; Dian Kartikasari (Unversitas Muhammadiyah Mataram, 2023)
Abstract: Intelligence is the application of cognitive aspects to learning and problem-solving processes, while cognitive processes depend on brain functions such as short-term memory, long-term memory. Based on interviews with the school principal, he said that there had never been an examination of cognitive abilities and the implementation of brain gymnastics on students. Brain gymnastics can improve cognitive skills (awareness, concentration, memory and executive function. Brain gymnastics is divided into 3 (three) functions, namely the lateral dimension, the dimension of concentration and the dimension of concentration. This study aims to determine the effect of brain gymnastics on the cognitive abilities of MTS Al Hikmah students Proto. The research design used the pre-experimental design method because it was not yet an actual experiment because there were still external variables that influenced the formation of the dependent variable. The research population was students of MTS Al-Hikmah Proto class 8A, while the research sample was students of MTS Al-Hikmah Proto class 8A with a total of 15 students.The research instrument used was the MoCa-Ina questionnaire.The results of statistical analysis using the T-test test obtained a P (Asymp. Sig. 2-tailed) of P=0.000 (P<0.05) so that Ho rejected, which means there is a significant effect on the brain exercise intervention on improving cognition f in grade 8A students at MTS Al-Hikmah Proto, Pekalongan Regency.Abstrak: Kemampuan kognitif merupakan fase perubahan yang terjadi selama hidup seseorang seperti memproses informasi, memecahkan masalah dan mengetahui sesuatu. Manfaat senam otak dapat meningkatkan keterampilan kognitif (kesadaran, konsentrasi, memori dan fungsi eksekutif). Penelitian ini bertujuan untuk mengetahui pengaruh senam otak terhadap kemampuan kognitif siswa MTS Al Hikmah Proto. Desain penelitian yang digunakan metode pre-experimental pretest-posttest one group. Sampel penelitian adalah siswa MTS Al-Hikmah Proto kelas 8A yang berjumlah 15 siswa yang dipilih menggunakan teknik purposive sampling. Untuk Instrumen penelitian yang digunakan yaitu kuesioner MoCa-Ina. hasil analisis statistik dengan menggunakan uji T-test didapatkan P (Asymp. Sig. 2-tailed) sebesar P=0,000 (P<0,05) sehingga Ho ditolak yang berarti ada pengaruh yang signifikan pada intervensi senam otak terhadap peningkatan kognitif pada siswa kelas 8A di MTS Al-Hikmah Proto Kabupaten Pekalongan. Diharapkan kepada pihak sekolah dan siswa agar tetap melaksanakan kegiatan senam otak 1 minggu sekali agar kognitif siswa tidak mengalami penurunan.